Advancing Forensic Science in Kazakhstan: The Emergence and Impact of Digital Forensics in Cybercrime Investigation - Saniyazova, Yerkemay; Mediyev, Renat; Saitova, Elmira; Utegenova, Gulzat; Kzylkhojayeva, Aisaulem (Law, State and Telecommunications Review, 2024)
[Purpose] The purpose of the article was to study digital forensics, its role in the Kazakh legal system and the process of investigating cybercrime. [Methodology] Analysis, synthesis, comparison, deduction, generalization, abstraction, formal legal methods of scientific research were used. [Findings] A result, it was proved that forensics is an indispensable component of the future development of forensic science in Kazakhstan. It has been established that digital forensics enables speeding up the process of solving cybercrimes, as well as determining their sources and prerequisites. Thus, on the basis of forensics, it is possible not only to identify the problem, but also to form a mechanism for overcoming it in the future. This determines the priority of professional training of forensic experts for future work with digital evidence, traces and their use in the trial. In addition, the areas of activity of law enforcement agencies has been established, in which forensics plays an important role and is mandatory for use.